1988
DOI: 10.1128/jvi.62.6.2050-2058.1988
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution of cells and viruses in a persistent infection of foot-and-mouth disease virus in cell culture

Abstract: Virus and cells evolve during serial passage of cloned BHK-21 cells persistently infected with foot-and-mouth disease virus (FMDV). These carrier cells, termed C1-BHK-Rcl (J. C. de la Torre, M. Da&vila, F. Sobrino, J. Ortin, and E. Domingo, Virology 145:24-35, 1985), become constitutively resistant to the parental FMDV C-S8c1. Curing of late-passage C1-BHK-Rcl cells of FMDV by ribavirin treatment (J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
89
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 31 publications
5
89
0
Order By: Relevance
“…On the other hand, data from FMDV persistent infections in cell cultures have revealed a co-evolution of both cell and resident virus [18] and a rapid phenotypic and genotypic variation of the host cells during the establishment of persistance [19]. Therefore, it has been suggested that a yet unidentified mechanism associated with virus replication could be responsible for this cellular genetic instability [19].…”
Section: Activationmentioning
confidence: 99%
“…On the other hand, data from FMDV persistent infections in cell cultures have revealed a co-evolution of both cell and resident virus [18] and a rapid phenotypic and genotypic variation of the host cells during the establishment of persistance [19]. Therefore, it has been suggested that a yet unidentified mechanism associated with virus replication could be responsible for this cellular genetic instability [19].…”
Section: Activationmentioning
confidence: 99%
“…The mechanisms that establish persistent infections in coronaviruses are still not understood; however, as with other RNA viruses, the interplay between virus and host may be the key to initiate persistence, which is then followed by the selection of a mutation to maintain the persistent infection [25][26][27][28]. Although there are some exceptions [24,[28][29]30], the general principle for establishment of virus persistence appears to be the attenuation virus gene expression and a restriction of cytopathic effect [25,29,31]. Whether there are mutations other than the one described above that might contribute to BCoV persistent infection remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular basis of persistence is largely unknown and is additionally complicated by the fact that various mechanisms seem to operate in different cell virus systems (reviewed in Holland, 1990;Oldstone, 1991;Ahmed et al, 1996). Persistently infected cell cultures represent a valuable tool to study the mechanisms of viral persistence and the molecular evolution of viruses and cells (de la Torre et al, 1985(de la Torre et al, , 1988. The latter aspect is especially interesting in the case of single-stranded RNA viruses which lack proofreading and postreplicative error correction mechanisms and are believed to have a high mutation rate (Lai, 1992;Domingo et al, 1996).…”
Section: Introductionmentioning
confidence: 99%